Online efficiency optimization of IPMSM for electric vehicles - Hanaa Elsherbiny; Mohamed Kamal Ahmed; Mahmoud A. Elwany (Institute of Advanced Engineering and Science, 2021)
This paper presents an online efficiency optimization method for the interior permanent magnet synchronous motor (IPMSM) drive system in an electric vehicle (EV). The proposed method considers accurately the total system losses including fundamental copper and iron losses, harmonic copper and iron losses, magnet loss, and inverter losses. Therefore, it has the capability to always guarantee maximum efficiency control. A highly trusted machine model is built using finite element analysis (FEA). This model considers accurately the magnetic saturation, spatial harmonics, and iron loss effect. The overall system efficiency is estimated online based on the accurate determination of system loss, and then the optimum current angle is defined online for the maximum efficiency per ampere (MEPA) control. A series of results is conducted to show the effectiveness and fidelity of proposed method. The results show the superior performance of proposed method over the conventional offline efficiency optimization methods.